PENGGUNAAN METODE MAKE A MATCH DALAM PEMBELAJARAN AQIDAH AKHLAK MI AL AZHAR DUKUH SETRO SURABAYA - Ainul Fithriyah (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2024)
Learning is said to be successful if students are involved in active learning activities and can interact with the teacher. Student activity greatly influences student learning outcomes. This research aims to increase student activity and learning outcomes by using the Make A Match method in learning Aqidah Akhlak. This type of research uses Classroom Action Research (PTK) with class IV subjects with a total of 20 students at MI Al Azhar Dukuh Setro Surabaya. This research went through four stages, namely planning, implementation, observation and reflection which were carried out in each cycle. The data collection techniques used were observation, interviews, documentation and field notes using teacher activity and student activity instrument sheets which were analyzed using descriptive qualitative and quantitative analysis. The results of the research were that, the results of teacher activity using the Make A Match method in Aqidah Akhlak learning in cycle I was 87% and increased in cycle II by 92.85%, student activity using the Make A Match method in cycle I was 62.5% and increased in cycle II by 95% in the very active category and student learning outcomes reached 55% in cycle I and increased by 45% in cycle II to 100%. It can be concluded from teacher activities, student activities can influence student learning outcomes to increase by using the Make A Match method in Learning Aqidah Akhlak MI Al Azhar Dukuh Setro Surabaya.